2014
DOI: 10.1007/s11431-014-5675-1
|View full text |Cite
|
Sign up to set email alerts
|

Wind tunnel test on aerodynamic effect of wind barriers on train-bridge system

Abstract: To investigate the aerodynamic effect of wind barriers on a high-speed train-bridge system, a sectional model test was conducted in a closed-circuit-type wind tunnel. Several different cases, including with and without barriers, with different barrier heights and porosity rates, and with different train arrangements on the bridge were taken into consideration; in addition, the aerodynamic coefficients of the train-bridge system were measured. It is found that the side force and rolling moment coefficients of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In 2003, to investigate the dynamic responses of the Antoing Bridge located on the high-speed railway line between Paris and Brussels subjected to Thalys trains, Xia et al performed a test by measuring the modal parameters, deflection, acceleration, strain of girder concrete and so on, which can be a reference for the study and the design of highspeed railway bridge [119]. During the next 15 years, plenty of research conducted by Shin et al [120], Guo et al [121], Wang et al [122] and so on, played an important role in assessing the running safety and ride comfort of the train-track-bridge dynamic system. The authors also have done many remarkable works in this field, one of which is illustrated for instance.…”
Section: Test For Assessing Safety Operation Of the Train-track-bridgmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2003, to investigate the dynamic responses of the Antoing Bridge located on the high-speed railway line between Paris and Brussels subjected to Thalys trains, Xia et al performed a test by measuring the modal parameters, deflection, acceleration, strain of girder concrete and so on, which can be a reference for the study and the design of highspeed railway bridge [119]. During the next 15 years, plenty of research conducted by Shin et al [120], Guo et al [121], Wang et al [122] and so on, played an important role in assessing the running safety and ride comfort of the train-track-bridge dynamic system. The authors also have done many remarkable works in this field, one of which is illustrated for instance.…”
Section: Test For Assessing Safety Operation Of the Train-track-bridgmentioning
confidence: 99%
“…The scaled model experiments conducted in wind tunnels were presented in Refs. [121,122,[174][175][176]. Through wind tunnel tests, some important parameters for numerical simulation, such as the aerodynamic coefficient of a vehicle and the flutter derivatives of a bridge, could be measured.…”
Section: Wind Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…A wind tunnel study on the wind barrier effects on a train-bridge system is reported (Guo et al 2015). They found that the side force and the rolling moment coefficients of the vehicle are efficiently reduced by a single side wind barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Han [5,6] made an accurate identification of the aerodynamic characteristics of vehicles and bridge at the premise of the coupled vibration analysis with a wind-vehicle-bridge system. Guo [7] found that the side force and rolling moment coefficients of the vehicle were efficiently reduced by a single-side wind barrier, but for the bridge deck these values were increased. Prud'homme [8] studied the influence between the sway movement and motion axis on flutter and vortex induced vibration in a 3 DOF wind tunnel test.…”
Section: Introductionmentioning
confidence: 99%